First record of the genus Lithophorus (Coleoptera: Bothrideridae) to Colombia and L. ornatus to South America. (2016)
The genus Lithophorus (Coleoptera: Bothrideridae) has previously been recorded in several countries in the Americas but not in Colombia. This study reports the finding of this genus with the species Lithophorus ornatus in Colombia for the first time. The species constitutes also a new record for South America.